Time evolution of short and intermediate term periodicities of electrons at geosynchronous orbit during solar cycle 23 and 24: A wavelet approach - Chowdhury P.; Dwivedi B.N. (My University, 2025)
In this paper, we investigate short and intermediate-term periodicities and their time variations in energetic electron flares at geosynchronous altitude in two different energy bands for the complete solar cycle 23 and a part of the current cycle 24 using data from Geostationary Operational Environmental Satellites (GOES). The wavelet power spectrum analysis method has been invoked to investigate time variation of the main quasi-periodicities present in the electron flux data. The wavelet power spectrum analysis shows a number of quasi-periodic oscillations in both data sets. In high frequency range, a prominent period of 22-35 day including 27 day oscillation is detected. Other quasi-periods in the range of 40-60 day, 90-100 day, near Rieger periods of 130-140, 180-190 day, Rieger period 150-160 day, ∼250 day, 350-370 day and 1.2-1.4 yr are found in different phases of cycle 23. In solar cycle 24, apart from other periods, we have detected the presence of best known Rieger period in both data sets. Possible explanations of the observed periodicities are discussed in terms of previous results and r-mode oscillations. © 2012 Elsevier Ltd. All rights reserved.